Laboratory and clinical reliability of two spectrophotometers - Klotz, Anna-Luisa; Habibi, Yasamin; Corcodel, Nicoleta; Rammelsberg, Peter; Hassel, Alexander J.; Zenthöfer, Andreas (Journal of esthetic and restorative dentistry, 2018)
To evaluate the repeatability, interexaminer, and interdevice reliability of two clinically applicable spectrophotometers under laboratory and clinical conditions.